Income Effects and Labor Supply - Evidence from a Swedish Property Tax Reform - Haggren,Ida; Henriksson,Lucas (2024)
This paper utilizes the 2008 capping of the Swedish property tax, which decreased the tax at different rates below and above the cap, to estimate the income effect. Using administrative data on over 600,000 individuals over twelve years, we employ a Difference-in-Differences approach and Coarsened Exact Matching to study how married cohabiting couples around the cap threshold respond to the reform. Our key finding is that the reform had a negative effect on the labor supply of individuals aged 55 and above, primarily driven by early retirement along the extensive margin where men respond more strongly than women. For individuals below age 55, we find no short-term labor supply response. The results have implications for policy design, in particular optimal tax policies around retirement ages.
Keywords: Income Effect; Labor Supply; Retirement; Property Tax; Difference-in-Difference